Hustlers and dynasties: exploring the role of anti-China populism in Kenya's 2022 elections - Hess, Steve; and Aidoo, Richard (Commonwealth and Comparative Politics, 2024)
The article examines William Ruto's use of a populist 'hustlers versus dynasties' campaign strategy and the degree to which this strategy incorporated anti-China rhetoric in his successful bid to win Kenya's presidency in August 2022. Building on fieldwor
Keywords: Africa; China; Democratization; Kenya; Populism